Measuring player pace of play in elite female association football - Bransen, L.; Davis, J. (International Journal of Sports Science & Coaching, 2025)
This research aims to understand how the differences in a football player's ability to cope with playing intensity may affect their chance of succeeding when transferring to a new league. Our hypothesis is that higher quality leagues exhibit a faster pace that affords players less time to control and play the ball. To measure this, we propose a novel pace-of-play metric that can be computed using match event data. It simply measures the amount of time a player takes to play a pass after gaining control of the ball either via receiving a pass or intercepting the ball. We assess the utility of our metric by analyzing five seasons of data about six top women's leagues. We make the following three findings. First, our metric is correlated with team strength as measured by Elo ratings. Second, our metric is correlated with the amount of playing time after an interleague transfer: players that exhibit a faster pace appear in a greater percentage of games in a new league. Third, as a measure of face validity, we show that our metric identified players who subsequently exhibited strong (e.g., prize winning) performance.